PERSEPSI PARA IBU TERHADAP SIKAP DONOR ASI DI BANDUNG - Tamadara Hilman (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This research is based on the low success rate in delivering exclusive breastfeeding in Bandung, 2019, which only reached 45%. This number is not in accordance with the government's target which stated in Government Regulation (PPRI) No. 33 of 2012. The cause of ineffectiveness of exclusive breastfeeding occurs due to several factors, such as the mother of the baby who died during childbirth, the mother of the baby who has infectious diseases such as HIV / AIDS, hepatitis and also the condition of babies who cannot breastfeed such as babies who have cleft lips. Awareness of the importance of human milk has led many parents to find human milk donors through social media in order to the babies get enough milk, meanwhile human milk donors on social media are not necessarily pass the medical examination. Based on the problem background that have been stated, this study aims to determine the perceptions of mothers towards the attitude in donating human milk. The method in this research is descriptive quantitative. The questionnaire was distributed to 350 mothers in Bandung. The results of the study show that the mother's perception has a positive and significant effect on the attitude in donating human milk, which is 63.3%.